Lawyers' Skills 2019
DOI: 10.1093/he/9780198838647.003.0001
|View full text |Cite
|
Sign up to set email alerts
|

1. Introduction

Abstract: This Guide is concerned with the lawyers’ skills that underpin practice as a solicitor and which are introduced during the Legal Practice Course (LPC). It serves as a supplement rather than a substitute for skills training undertaken on the LPC. This introductory chapter briefly discusses the nature of legal skills training and then provides instructions on how to use the present Guide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Lawyers act in a complex and dynamic occupational environment (Bronstein and Solomon, 2021; Flood, 2019) distinguished by a vast and growing scope of information (Jamshed, 2020; Van Opijnen and Santos, 2017), and they engage in diverse information practices and channels (Bronstein and Solomon, 2021). Lawyers must know how to obtain current, reliable and relevant information to the actual cases presented to them, to solve the legal issues involved (Chancellor, 2010; Cohen and Olson, 2018; Krieger et al, 2020; Webb et al, 2019; Wilkinson, 2001) and provide efficient and trustworthy legal services to their clients (Nwagwu and Ajibade, 2021). In that regard, Solomon and Bronstein (2022) demonstrated that lawyers might employ several strategies to gather information in the course of their legal work.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Lawyers act in a complex and dynamic occupational environment (Bronstein and Solomon, 2021; Flood, 2019) distinguished by a vast and growing scope of information (Jamshed, 2020; Van Opijnen and Santos, 2017), and they engage in diverse information practices and channels (Bronstein and Solomon, 2021). Lawyers must know how to obtain current, reliable and relevant information to the actual cases presented to them, to solve the legal issues involved (Chancellor, 2010; Cohen and Olson, 2018; Krieger et al, 2020; Webb et al, 2019; Wilkinson, 2001) and provide efficient and trustworthy legal services to their clients (Nwagwu and Ajibade, 2021). In that regard, Solomon and Bronstein (2022) demonstrated that lawyers might employ several strategies to gather information in the course of their legal work.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lawyering is an information-intensive liberal profession (Bronstein and Solomon, 2021). A lawyer’s legal work necessitates extensive and varied information (Krieger et al, 2020; Webb et al, 2019) gathered via various sources that grow in number and complexity (Leckie et al, 1996; Nwagwu and Ajibade, 2021; Rao, 2019). The latter encompasses, among other things, “human,” “printed,” and “electronic” sources of information, along with “internal” and “external” to the lawyer’s practice and “formal” and “informal” ones (Solomon and Bronstein, 2016; Wilkinson, 2001).…”
Section: Introductionmentioning
confidence: 99%